Entrepreneurship education and entrepreneurial self-efficacy of students at UiTM Sarawak / Kuldip Singh. - Singh, Kuldip (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
Although entrepreneurship education has been offered in higher education institutions (HEIs) for more than two decades, graduates, particularly Bumiputera graduates, are less willing to become entrepreneurs. The implementation of entrepreneurship education in universities also seems to have failed to nurture and develop the characteristics and quality of entrepreneurship among students. This study examines the relationship between entrepreneurship education and entrepreneurial self-efficacy amongst undergraduate students in UiTM Sarawak. For this study one hundred and seventy (170) usable questionnaires were collected and analysed accordingly to test the various hypotheses. The measurement items were rated with 5-point Likert. Goodness of measures were performed with SPP software and all the item measures were found to be reliable and valid. The results indicate that entrepreneurship education is positively correlated with entrepreneurial self-efficacy. In addition the study also found no significant differences in entrepreneurial self-efficacy based on gender. These results imply that entrepreneurship education in UITM Sarawak is highly correlated with entrepreneurial selfefficacy and that gender does not make a significant difference in the level of entrepreneurial self-efficacy. This study provides insights on the relationship between entrepreneurship education and entrepreneurial self-efficacy in higher education institutions (HEIs) The findings of this study can help the higher education institutions (HEIs) to better understand entrepreneurship education and its effect on entrepreneurial self-efficacy.